Changing climate reallocates the carbon debt of frequent‐fire forests - Goodwin, Marissa J.; North, Malcolm P.; Zald, Harold S. J.; Hurteau, Matthew D. (Global change biology, 2020)
Ongoing climate change will alter the carbon carrying capacity of forests as they adjust to climatic extremes and changing disturbance regimes. In frequent‐fire forests, increasing drought frequency and severity are already causing widespread tree mortality events, which can exacerbate the carbon debt that has developed as a result of fire exclusion. Forest management techniques that reduce tree density and surface fuels decrease the risk of high‐severity wildfire and may also limit drought‐induced mortality by reducing competition. We used a long‐term thinning and burning experiment in a mixed‐conifer forest to investigate the effects of the 2012–2015 California drought on forest carbon dynamics in each treatment, including the carbon emissions from a second‐entry prescribed fire that followed the drought. We assessed differences in carbon stability and tree survival across treatments, expecting that both carbon stability and survival probability would increase with increasing treatment intensity (decreasing basal area). Additionally, we analyzed the effects of drought‐ mortality on second‐entry burn emissions and compared emissions for the first‐ and second‐entry burns. We found a non‐linear relationship between treatment intensity and carbon stability, which was in part driven by varying relationships between individual tree growing space and survival across treatments. Drought mortality increased dead tree and surface fuel carbon in all treatments, which contributed to higher second‐entry burn emissions for two of the three burn treatments when compared to the first burn. Our findings suggest that restoration treatments will not serve as a panacea for ongoing climate change and that the carbon debt of these forests will become increasingly unstable as the carbon carrying capacity adjusts to severe drought events. Managing the carbon debt with prescribed fire will help reduce the risk of additional mortality from wildfire, but at an increasing carbon cost for forest management. We used a long‐term thinning and burning experiment to quantify the effects of forest restoration treatments on carbon stability during the 2012–2015 California drought and the carbon emissions of a second‐entry prescribed burn that followed. We found that drought‐related mortality reduced live tree carbon across all treatments, with corresponding increases in dead tree and surface fuel carbon pools. The second‐entry burn (2017) consumed dead trees and surface fuels which reduced the wildfire risk associated with drought‐related fuel inputs. However, higher second‐entry burn emissions in two of the burn treatments suggest climate change may increase the carbon cost of forest management.